E_Story Book as a Means of Reading Habitation during the Covid-19 Pandemic at SMP Negeri 4 Banyumas - Setianingsih, Dwi Riyani Darma; Suharto, Abdul Wachid Bambang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
One way to improve reading skills is to get into the habit of reading fiction books regularly. This study aims to analyze the use of e-story books to read habituation and its benefits for students of SMP Negeri 4 Banyumas. The method used is the descriptive method. Data collection methods are interviews, monitoring questionnaires and written data. Interviews were conducted with the person in charge of the activity and the activity coordinator. Meanwhile, questionnaires were distributed to all students at SMP Negeri 4 Banyumas from class VII, VIII, and class IX. The results showed that students at SMP Negeri 4 Banyumas liked the habit of reading fiction books using E-Story Books. The benefits of habituation activities to read fiction books using E-Story Books for students, among others, can be a means for students to channel hobbies, add insight, and students' skills in reading and understanding the content of a lesson.